PENERAPAN EFEKTIVITAS GAYATRI EMOTIONAL FREEDOM TECNIQUE UNTUK MENGATASI KELELAHAN KERJA PERAWAT HEMODIALISA RUMAH SAKIT BHAYANGKARA TK.I R.SAID SUKANTO JAKARTA - Anjani Dara Narulita, (2023)
Work fatigue is the body's natural mechanism of protection to avoid further damage so that recovery occurs after rest. The results of the author's observations in the hemodialysis room of Bhayangkara Kindergarten Hospital. I R.Said Sukanto Jakarta, a nurse has shift working for 12 hours by doing nursing care to 3-6 patients a day. This is in line with the results of the questionnaire that has been distributed by the author using the questionnaire Industrial Fatique Research Commitee Of Japan Association Of Industrial Health (IFRS) showed that there were 6 nurses (67%) in the low work fatigue category and 3 nurses (33%) in the high work fatigue category. Based on these results, the author applied evidence-based practice nursing by providing emotional freedom technique therapy to nurses who felt high work fatigue. The application of gayatri emotional freedom technique therapy is carried out for 3 days with a duration of 10 minutes. Post-test results after GEFT therapy resulted in a decrease in the category of high work fatigue to the category of low work fatigue in 3 nurses (100%). With these results, it is proven that the application of the effectiveness of emotional freedom technique therapy can overcome nurses' work fatigue. It is expected that nurses can do emotional freedom technique therapy when feeling work fatigue after doing nursing care to patients.